Effects of relational benefits in the model of customers' benefits and relationship quality in Vietnam - Phuong T. Nguyen; Hieu V. Cao; Hiep M. Phuoc; Phong T. Tran (Economies, 2022)
With the aim of comparing the influence of economic benefits with social benefits in the model of integrating customer benefits and relationship quality in the context of university-enterprise relationship research in Ho Chi Minh City (HCMC), Vietnam. From the perspective of enterprises, a study combining qualitative and quantitative research was carried out. Data for the main study were collected from 486 enterprises using an online survey. The research model and hypotheses are tested by analyzing the structural equation model. The results of examining the influence of economic benefits and social benefits in the research model indicate that the influence of economic benefits is more significant than the influence of social benefits. This is a new finding of this study in comparison with previous studies on relational benefits. In addition, the study also pointed out that economic benefits and social benefits have a direct impact on perceived service quality.
Keywords: 330; customer loyalty; perceived service quality; relational benefits; relationship quality